Medicare for you : a smart person's guide - Omdahl, Diane J. (Humanix Books, 2023)
"Every day, over 10,000 Americans will become eligible for Medicare, but most of us don't even know the basics. When do I enroll? What does it cover? Do I need Part B? You could watch the commercials or reply to direct mail. You could ask your best friend. Or you can take charge of these very important decisions and READ THIS BOOK! Medicare expert Diane J. Omdahl will take you through all the steps to making the right decisions at the right time. Avoid costly mistakes and scams and ensure that Medicare works for you." -- Back cover.